Use of complementary and alternative medicine in a sample of women with breast cancer - Vidal, Mariana (2013)
Abstract This study aims to examine the usage of complementary and alternative medicine (CAM) on a sample of Portuguese women with history of breast cancer. A total of 107 women with history of breast cancer attending Movimento Vencer e Viver Lisboa responded to a questionnaire designed to assess the use of CAM, as well as other variables, such as satisfaction with conventional care, health perception, perceived control over cancer, and health status (body mass index [BMI], smoking and alcohol consumption, hours of sleep, and physical activity). Forty-eight percent of the participants had used some kind of CAM in the past 12 months. The perceived control over cancer was significantly associated with CAM use (odds ratio [OR] = 1.5; 95% confidence interval [CI] = [1.2, 1.9]). CAM use was more prevalent among women aged 30 to 39 years, single, with high education, and a monthly income of 2,500€ to 2,999€. The CAM used most often were natural products, along with psychotherapy, breathing exercises, and meditation. The main reason mentioned for its use was the improved sense of wellbeing, and it was interesting to note that 60% of the participants who used CAM did not discuss it with their physicians. The findings support previous data that suggest that the participants’ perceived control over their cancer is a significant predictor of CAM usage, and more than half of the patients did not discuss CAM usage with their physician. Further studies with larger samples of cancer patients are warranted.